Air–water gas exchange in lakes and reservoirs measured from a moving platform by underwater eddy covariance. (30th June 2020) - Berg, Peter; Pace, Michael L.; Buelo, Cal D.
Abstract: Air–water exchange rates of gasses, such as O2, CO2, and CH4, are widely used in ecosystem studies of lakes and reservoirs, but their magnitudes are often difficult to assess. In this proof‐of‐concept study, we measured gas exchange by underwater eddy covariance in such lentic systems from a moving platform. We used an Acoustic Doppler Velocimeter and a fast‐responding O2 ‐temperature sensor mounted in the bow of a boat to measure water velocity, O2 concentration, and temperature below the air–water interface ( 10 cm) while the boat was propelled at constant speed ( 25 cm s −1 ) by an electric trolling motor. Fluxes of O2 and heat across the air–water interface and standard gas exchange coefficients, k 600, were calculated for every 3 min of traveled distance ( 45 m). All deployments were done under calm low‐wind conditions where empirical relationships for k 600 are most uncertain. Deployment averages of k 600 ranged from 0.070 to 0.39 m d −1 and were strongly correlated with both the heat flux and the water temperature. In one deployment, a > 20% variation in mean water column O2 concentration was measured along a 1 km long transect of a reservoir. Given the typical size of O2 concentration differences over the air–water interface that drive gas exchange, such lateral variations can, even at a near‐constant exchange coefficient, result in highly biased whole‐ecosystem fluxes if based on stationary single‐point O2 measurements. "Mobile" aquatic eddy covariance measurements enable quantification of gas exchange in lakes and reservoirs under true in situ conditions and with high temporal and spatial resolution.